Efficient conversion of chitosan into 5-hydroxymethylfurfural via hydrothermal synthesis in ionic liquids aqueous solution. (November 2015) - Li, Mingguang; Zang, Hongjun; Feng, Jiaxuan; Yan, Qing; Yu, Nianqin; Shi, Xiaolong; Cheng, Bowen
Abstract: A new process for the efficient conversion of chitosan into 5-hydroxymethylfurfural (5-HMF) has been developed. Chitosan was hydrolyzed in the presence of acidic ionic liquids (ILs), with N-methyl imidazolium hydrogen sulfate ([MIM]HSO4 ) giving the best results. The effects of reaction time, temperature and quantity of water and IL were investigated in detail. The optimal reaction conditions were found to be 4wt % IL ([MIM]HSO4 ) aqueous solution under hydrothermal condition, 180 °C and a reaction time of 5 h. A yield of 29.5 mol% 5-HMF was obtained from 100 mg chitosan. Furthermore, chitosan with different molecular weight could be directly converted into 5-HMF in good yields under these conditions. More importantly, [MIM]HSO4 could be recovered by simple post-processing and exhibited constant activity over 5 cycles.